INTEGRATION OF QUR'ANIC VALUES THROUGH THE MPKQI MODEL FOR CHARACTER STRENGTHENING AMID THE MORAL CRISIS - Daffa Akmal, Mochamad; Rika Sa’diyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop the Integrative Qur'anic Islamic Education Management Model (MPMQI) as a strategy for strengthening students’ character amid the global moral crisis. The moral crisis, characterized by increasing individualism, ethical degradation, misuse of digital technology, and the weakening of spiritual values, indicates that education has not fully succeeded in shaping students’ character holistically. This research employed a qualitative approach using the library research method by analyzing various relevant literature on Qur’anic values, Islamic educational management, and character education. The findings reveal that Qur’anic values such as tawhid (monotheism), trustworthiness (amanah), honesty, justice, responsibility, and ihsan (excellence) can be integrated into all functions of Islamic educational management, including planning, organizing, implementing, and evaluating. This integration results in the development of the Integrative Qur'anic Islamic Education Management Model (MPMQI), which focuses on character formation through value internalization, the establishment of an Islamic organizational culture, educators’ role modeling, positive behavioral habituation, and the wise utilization of technology. The model positions Qur’anic values as the primary foundation of educational management, thereby creating a conducive learning environment for character development. Furthermore, MPMQI contributes not only to improving the quality of Islamic educational management but also serves as a strategic solution for developing a generation that possesses noble character, integrity, and the ability to respond to global challenges while maintaining its Islamic identity. Therefore, the implementation of MPMQI is expected to strengthen the role of Islamic education in addressing contemporary moral challenges and fostering sustainable character developmen.